Comparative Value of Simple Inflammatory Markers in the Prediction of Left Ventricular Systolic Dysfunction in Postacute Coronary Syndrome Patients - Panagiotis Aggelopoulos; Christina Chrysohoou; Christos Pitsavos; Lambros Papadimitriou; Catherine Liontou; Demosthenes Panagiotakos; Eleftherios Tsiamis; Christodoulos Stefanadis (Mediators of Inflammation)
Objectives. We sought to assess the comparative value of inflammatory markers on the occurrence of left ventricular systolic dysfunction (LVSD) after an acute coronary syndrome (ACS). Methods. During 2006–2008, 760 patients with an ACS were enrolled. C-reactive protein (CRP) and white blood cell (WBC) count were measured during the first 12 hours of hospital admission. Results. CRP levels and WBC count were significantly higher in those who developed LVSD compared to those who did not. The analysis revealed that a 10 mg/dL increase of CRP levels and a 1000/𝜇L increase in WBC are associated with a 6% and a 7% increase in the likelihood of developing LVSD, respectively. Furthermore, WBC count at entry and CRP have almost the same predictive value for development of LVSD after an ACS (𝑅2=0.109 versus 𝑅2=0.093). Conclusions. Serum CRP levels and WBC count at entry are almost equally powerful independent predictors of LVSD, after an ACS.